KONSERVASI TRADISIONAL TERHADAP SUMBER DAYA ALAM DI DESA LINGAT KECAMATAN SELARU - Audrey Lodowina Labobar; Ernywati Badaruddin; Maya M. S. Puttileihalat (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to determine the Traditional Conservation of Natural Resources in Lingat Village, Selaru District. The study took place from March to April 2025. In relation to the implementation of this research, the method used is the Survey method with descriptive analysis which is to describe systematically, factually and accurately about the local wisdom of the Lingat village community with Traditional Conservation management. The Data used in this study include primary data and secondary data. In this study also conducted data collection in the form of interviews with the public by using questionnaires as a guide questions and direct observation. In addition to interviews to get in-depth results, observations and documentation are also carried out so that the data obtained is more accurate in accordance with the data obtained at the time of the study. The results showed that the local wisdom of the Indigenous people of Lingat village in the management of natural resources related to Traditional Conservation includes beliefs and or abstinence.